Emotional intelligence and cognitive need in university students - Escurra Mayaute, Luis Miguel (2001)
It is analized the relationship between emotional intelligence and need for cognition considering Freshmen college students of a public peruvian university (Universidad Nacional Mayor de San Marcos). The participants were 365 students of the 19 schools and five major academic areas. it was found differences among men and women on emotional intelligence. Also, there were differences on specific areas such as empathy, emotional self knowledge, and self motivation. Considering the need for cognition it was found no differences among women and men. Finally, it was found positive correlations between the scores of emotional intelligence and need for cognition.